2018
DOI: 10.1101/467225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals a dynamic stromal niche within the evolving tumour microenvironment

Abstract: Non-cancerous stromal cells represent a highly diverse compartment of the tumour, yet their role across tumour evolution remains unclear. We employed single-cell RNA sequencing to determine stromal adaptations in murine melanoma at different points of tumour development. Naive lymphocytes recruited from lymph nodes underwent activation and clonal expansion within the tumour, prior to PD1 and Lag3 expression, while tumourassociated myeloid cells promoted the formation of a suppressive niche through cytokine sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Functional annotation using GSVA analysis (SuppFig. 7A) revealed that secretory FC0 were governed by hallmarks of EMT and were enriched for a desmoplastic signature 37 , characterised by genes involved in extra cellular matrix (ECM)…”
Section: Characterisation Of Cancer-associated Fibroblasts In Pymt Tumentioning
confidence: 99%
See 1 more Smart Citation
“…Functional annotation using GSVA analysis (SuppFig. 7A) revealed that secretory FC0 were governed by hallmarks of EMT and were enriched for a desmoplastic signature 37 , characterised by genes involved in extra cellular matrix (ECM)…”
Section: Characterisation Of Cancer-associated Fibroblasts In Pymt Tumentioning
confidence: 99%
“…5C and D). Secretory FC1 clearly showed immune-related functions (top enriched hallmarks "Interferon alpha response", "IL6/JAK/STAT3 signalling" and "Interferon gamma response"), with genes involved in cytokine-cytokine receptor interactions, monocyte recruitment and the complement cascade 37 . FC2 were enriched for a contractile signature, characterised by the expression of genes involved in actin cytoskeleton organisation.…”
Section: Characterisation Of Cancer-associated Fibroblasts In Pymt Tumentioning
confidence: 99%
“…For example, CellPhoneDB helped us identify a shift in the cellular communication from a network that was dominated by mesenchymal-epithelial interactions in healthy airways, to a Th2 cell--dominated interactome in asthmatic airways 2 . In another recent 40 example, our cell-cell communication framework revealed the complex interplay among diverse cells in the evolving tumor microenvironment of a murine melanoma model where multiple immunosuppressive mechanisms coexist within a heterogeneous stromal compartment 3 . We anticipate that the information stored in CellPhoneDB 2.0 will have the potential to resolve cellular communication when combined with the spatial location of the cells that can be quantified using highly multiplexed spatial methods [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…To test northstar's performance on a larger cancer dataset, we analyzed 4,626 cells from a melanoma murine model focused on infiltrating immune cells 21 . As with the GBM data, we found high accuracy with the default parameters (~ 90% correctly assigned immune cells using Tabula Muris marrow annotations only).…”
Section: Benchmark Against Published Datasets On Healthy Brain and Glmentioning
confidence: 99%